The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10584-009-9545-y
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability and the Peruvian scallop fishery: the role of formal institutions in resilience building

Abstract: Peru experiences recurrent ENSO (El Niño Southern Oscillation) events during which the Peruvian bay scallop (Argopecten purpuratus) undergoes substantial changes in its stock size. In the North of the country strong warm ENSO events are synonymous with floods and river discharges that negatively affect scallop biomass, while in the South increased sea surface temperatures lead to an increase in stock size. This paper explores how formal institutions respond to climate variability and resource fluctuations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…Particularly in Peruvian beaches, the strong 1982/1983 and 1997/1998 El Niño events caused mass mortalities of surf clam (Arntz et al 1987). The same differential response to extreme events was observed for the artisanally harvested Peruvian bay scallop (Argopecten purpuratus): in the north of Peru, strong El Niño events drastically increased floods and river discharges, causing a decrease in scallop biomass, whereas increasing temperatures in the south produced a positive effect on stock size (Badjeck et al 2009). During the 1997/1998 El Niño event, Independence Bay (14ºS, Peru) showed a 10ºC increase in sea surface temperature (SST), high oxygen concentrations, and diminished phytoplankton concentrations.…”
Section: Shellfisheriesmentioning
confidence: 74%
See 1 more Smart Citation
“…Particularly in Peruvian beaches, the strong 1982/1983 and 1997/1998 El Niño events caused mass mortalities of surf clam (Arntz et al 1987). The same differential response to extreme events was observed for the artisanally harvested Peruvian bay scallop (Argopecten purpuratus): in the north of Peru, strong El Niño events drastically increased floods and river discharges, causing a decrease in scallop biomass, whereas increasing temperatures in the south produced a positive effect on stock size (Badjeck et al 2009). During the 1997/1998 El Niño event, Independence Bay (14ºS, Peru) showed a 10ºC increase in sea surface temperature (SST), high oxygen concentrations, and diminished phytoplankton concentrations.…”
Section: Shellfisheriesmentioning
confidence: 74%
“…Changes in climatic drivers might directly favor certain species over others, based on their latitudinal distribution and the oceanographic features of the area (Badjeck et al 2009). Indeed, a recent evaluation of the surf clam (Mesodesma donacium) in the Pacific (distribution range from 5ºS to 42º S) suggested that warm ENSO (El Niño) events negatively affected landings in Peru and northern Chile (Fig.…”
Section: Shellfisheriesmentioning
confidence: 99%
“…Otra respuesta diferencial a los eventos climáticos extremos se observó para el ostión o concha de abanico Argopecten purpuratus explotada artesanalmente en el norte de Perú: los eventos severos de El Niño aumentaron drásticamente las inundaciones y descargas de los ríos, provocando una disminución en la biomasa del ostión, mientras que el aumento de las temperaturas en el Sur produjo un aumento de su población (Badjeck et al, 2009). Durante el evento de El Niño 1997-98, la SST en la Bahía de la Independencia (14ºS, Perú) aumentó 10ºC y se registraron altas concentraciones de oxígeno y concentraciones reducidas de fitoplancton.…”
Section: Las Almejas Del Género Mesodesmaunclassified
“…Climatic drivers, such as El Niño Southern Oscillation (ENSO), affect habitats and ecological patterns and processes of target and non-target species, causing changes in habitat suitability, biogeography and demography, as well as modifi cations to dispersal, feeding, growth and behavioral patterns (Badjeck et al 2009 ;Ortega et al 2012 ). The negative changes induced by climatic drivers (e.g., mass mortalities) are exacerbated by human drivers (i.e., market globalization and weak governance), leading to loss of resilience in small-scale shellfi sheries .…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge is important to understand how co-governance institutions and actors learn, self-organize and respond to diverse climatic and human drivers, as well as to design policies aimed at maintaining or increasing resilience in small-scale fi sheries (Adger et al 2005 ;Badjeck et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%